Gut microbiota and type 1 diabetes: a two-sample bidirectional Mendelian randomization study - Luo, Manjun; Sun, Mengting; Wang, Tingting; Zhang, Senmao; Song, Xinli; Liu, Xiaoying; Wei, Jianhui; Chen, Qian; Zhong, Taowei; Qin, Jiabi (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: The real causal relationship between human gut microbiota and T1D remains unclear and difficult to establish. Herein, we adopted a two-sample bidirectional mendelian randomization (MR) study to evaluate the causality between gut microbiota and T1D. Methods: We leveraged publicly available genome-wide association studies (GWASs) summary data to perform MR analysis. The gut microbiota-related GWASs data from 18340 individuals from the international consortium MiBioGen were used. The summary statistic data for T1D (n = 264137) was obtained from the latest release from the FinnGen consortium as the outcome of interest. The selection of instrumental variables conformed strictly to a series of pre-set inclusion and exclusion criteria. MR Egger, weighted median, inverse variance weighted (IVW), weighted mode methods were used to assess the causal association. The Cochran’s Q test, MR-Egger intercept test and leave-one-out analysis were conducted to identify heterogeneity and pleiotropy. Results: At the phylum level, only Bacteroidetes was indicated to have causality on T1D (OR = 1.24, 95% CI = 1.01-1.53, P = 0.044) in the IVW analysis. When it comes to their subcategories, Bacteroidia class (OR = 1.28, 95% CI = 1.06-1.53, P = 0.009, PFDR = 0.085), Bacteroidales order (OR = 1.28, 95% CI = 1.06-1.53, P = 0.009, PFDR = 0.085) and Eubacterium eligens group genus (OR = 0.64, 95% CI = 0.50-0.81, P = 2.84×10-4, PFDR = 0.031) were observed to have causal relationship with T1D in the IVW analysis. No heterogeneity and pleiotropy were detected. Conclusions: The present study reports that Bacteroidetes phylum, Bacteroidia class, Bacteroidales order causally increase T1D risk, whereas Eubacterium eligens group genus, which belongs to Firmicutes phylum, causally decreases T1D risk. Nevertheless, future studies are warranted to dissect the underlying mechanisms of specific bacterial taxa’s role in the pathophysiology of T1D.